Pendampingan Penyusunan Organisasi dan Kelembagaan Pengelola Obyek Wisata Alam Pulau Semut - Eno Suwarno; Rina Novia Yanti; Bambang Supeno (Universitas Lancang Kuning, 2022)
The tourism sector is currently the government's flagship program, one of which is ecotourism. Inaccordance with government regulations, the development of natural tourism is required to empower localcommunities through the active role of the community in planning, utilization, and control activities.Communities who are members of the Pengambang Hamlet Tourism Awareness Group are currently activelyworking together to build the Semut Island ecotourism object on the banks of the Siak River. They still need alot of help from other parties, one of which is assistance in the preparation of organizational andinstitutional structures. This task was carried out by the Lancang Kuning University Service Team. Thepreparation of the organizational structure is carried out through a deliberation process, where themanagement is filled by all active members. Meanwhile, the institutional arrangement is in the form of draftregulations which will later become the material for the Articles of Association and Bylaws. Assistance topartners requires a long duration of time along with the stages of development to the stage of operating inan established manner. Therefore, assistance for managing the organization and making the Articles ofAssociation and Bylaws is still needed.